Reaction of SO2 with OH in the atmosphere. Issue 11 (7th March 2017) - Long, Bo; Bao, Junwei Lucas; Truhlar, Donald G.
Abstract : We theoretically investigate the rate constant k ( T, p ) of the OH + SO2 reaction with experimental accuracy. Abstract : The OH + SO2 reaction plays a critical role in understanding the oxidation of SO2 in the atmosphere, and its rate constant is critical for clarifying the fate of SO2 in the atmosphere. The rate constant of the OH + SO2 reaction is calculated here by using beyond-CCSDT correlation energy calculations for a benchmark, validated density functional methods for direct dynamics, canonical variational transition state theory with anharmonicity and multidimensional tunneling for the high-pressure rate constant, and system-specific quantum RRK theory for pressure effects; the combination of these methods can compete in accuracy with experiments. There has been a long-term debate in the literature about whether the OH + SO2 reaction is barrierless, but our calculations indicate a positive barrier with an transition structure that has an enthalpy of activation of 0.27 kcal mol −1 at 0 K. Our results show that the high-pressure limiting rate constant of the OH + SO2 reaction has a positive temperature dependence, but the rate constant at low pressures has a negative temperature dependence. The computed high-pressure limiting rate constant at 298 K is 1.25 × 10 −12 cm 3 molecule −1 s −1, which agrees excellently with the value (1.3 × 10 −12 cm 3 molecule −1 s −1 ) recommended in the most recent comprehensive evaluation for atmospheric chemistry. We show that the atmospheric lifetime of SO2 with respect to oxidation by OH depends strongly on altitude (in the range 0–50 km) due to the falloff effect. We introduce a new interpolation procedure for fitting the combined temperature and pressure dependence of the rate constant, and it fits the calculated rate constants over the whole range with a mean unsigned error of only 7%. The present results provide reliable kinetics data for this specific reaction, and also they demonstrate convenient theoretical methods that can be reliable for predicting rate constants of other gas-phase reactions.